Effects of Myostatin b Knockout on Offspring Body Length and Skeleton in Yellow Catfish (Pelteobagrus fulvidraco) - Xincheng Zhang; Fang Wang; Mi Ou; Haiyang Liu; Qing Luo; Shuzhan Fei; Jian Zhao; Kunci Chen; Qingshun Zhao; Kaibin Li (Biology, 2023)
Based on obtaining mstnb gene knockout in Pelteobagrus fulvidraco, a study on the effect of the mstn gene on skeletal morphology and growth was performed by comparing the number and length of the vertebrae of mutant and wild-type fish in a sibling group of P. fulvidraco, combined with the differences in cells at the level of vertebral skeletal tissue. It was found that mstnb gene knockdown resulted in a reduction in the number of vertebrae, the length, and the intervertebral distance in P. fulvidraco, and these changes may be the underlying cause of the shorter body length in mutant P. fulvidraco. Further, histological comparison of the same sites in the mstn mutant and wild groups of P. fulvidraco also revealed that the number and density of osteocytes were greater in mstnb knockout P. fulvidraco than in wild-type P. fulvidraco. Our results demonstrated that when using genome editing technology to breed new lines, the effects of knockout need to be analyzed comprehensively and may have some unexpected effects due to insufficient study of the function of certain genes.